ENGLISH 1 TEACHERS SELF-PERCEIVED CLASSROOM ASSESSMENT SKILLS QUALITY AND PRACTICES & STANDARDS OF HIGHER EDUCATIONAL INSTITUTIONS IN BALUCHISTAN, PAKISTAN - Ali Murtaza; Ajaz Shaheen; Ahmed, Rafiq (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
The quality education is fundamental priority of every institution which only be developed through the absolute assessment skills quality and effective standers & practices in assessment process. This study was conducted from the ten higher educational institutions. Questionnaires were distributed among the respondents of the study as a research tool and data was analyzed and assessed quantitatively. This study examines that teacher self perceived classroom assessment skills in contrast of standards & practices of assessment at higher educational institutions are ineffective and less reliable in nature; it could not rightly access & evaluate the true potential and improving capacity of performance of students, it directly affects the quality education and reputation of the institution. It has been intensively over sighted that teachers self perceived classroom assessment skills quality is lacking and inefficient with respect of standards and policy of HEI and HEC. Higher education commission has well framed the guidelines and road map of assessment for higher educational institutions. HEC conducts different training sessions & programs for teachers to enhance their assessment expertise, quality skills and make professional sense among the teachers for effective & efficient skills of assessment despite of that teacher do not realize the essence of assessment in quality education.